AUTHORITY OF THE NOTARY IN MAKING CERTIFICATE OF INHERITANCE FOR INDONESIAN CITIZENS - Hanifah; Gunawan Djajaputra (RADJA PUBLIKA, 2023)
This article aims to discuss the authority of a notary regarding the making of an inheritance certificate for Indonesian citizens and the legal certainty of an inheritance certificate for Indonesian citizens made by a notary based on Article 106 of Law Number 23 of 2006 as Amended by Law Number 24 of 2006. 2013 concerning Population Administration. This article uses normative legal research methods. The nature of the research is descriptive analysis. The primary legal materials used in this study are the 1945 Constitution of the Republic of Indonesia, Law Number 12 of 2006 concerning Citizenship, Law Number 23 of 2006 as amended by Law Number 24 of 2013 concerning Population Administration, Regulation of the Minister of Agrarian Affairs/Regulation of the Head of the National Land Agency Number 16 of 2021 concerning the third Amendment to Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for Implementing Government Regulation No. 24 of 1997 concerning Land Registration, Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notary. The secondary legal materials include textbooks, legal dictionaries, legal journals, and comments on court decisions. The tertiary legal materials used in this study are the Big Indonesian Dictionary and the Legal Dictionary. The results of the study show that the Notary's Authority in making inheritance certificates for Indonesian citizens is valid. Because a Notary as a public official is given the authority to carry out some of the state's duties in making authentic evidence in the field of civil law whose authority is regulated in a separate regulation. The legal certainty of a certificate of inheritance for Indonesian citizens made by a Notary has perfect evidentiary power.